Earth(l)y pleasures and air-borne bodies: Elemental haptics in women's cross-country running - Allen-Collinson, J.; Jackman, P. C. (International Review for the Sociology of Sport, 2022)
A rich and multi-stranded sociology of sporting embodiment has begun to emerge in recent years. Calls have been made to analyze more deeply not only the sensory dimensions of lived sporting bodies but also the values prevailing within particular physical-cultural worlds. This article contributes to a small, developing research corpus by employing theoretical perspectives drawn from phenomenological sociology to explore cross-country runners' sensory encounters with the elemental, contoured by the values of the running lifeworlds they inhabit. Autoethnographic and autophenomenographic data were collected via three research projects. Senses of touch still remain under-researched within the sporting sensorium, and here we focus on the "elemental haptics" of earth and air on our cross-country training runs. We also explore the rich, complex somatic experiences afforded by various of these elemental combinations. For runners, as for many sports participants, the haptic emerges as a key aspect of our sensuous running lifeworld.